THE EFFECTIVENESS OF USING TWO STAY TO STRAY TECHNIQUES IN TEACHING READING COMPREHENSION FOR STUDENTS OF SMP IT IBNU SINA MERAUKE - Rezky Uspayanti; Sandra Ika Sulistiawati; Marni Bawawa; Margaretha F Narahawarin (PT Akselerasi Karya Mandiri, 2025)
This research examined the effectiveness of the Two Stay Two Stray (TSTS) technique in enhancing reading comprehension among students at SMP IT Ibnu Sina Merauke in the 2024/2025 academic year. This research employed pre-experimental research with one-group pretest-posttest. The sample was 28 students. Data were analyzed using descriptive statistics. In collecting the data, the researchers used a reading comprehension test in the form of multiple choice. Creating a multiple-choice question (MCQ) test with pre-test and post-test for assessing reading comprehension of narrative texts. The results demonstrated a statistically significant difference in students' reading comprehension between the pre-test with the result of mean score was 74.43 and post-test with the result of the mean score was 89.21. Furthermore, the research accepted the alternative hypothesis (H₁): the implementation of the Two Stay Two Stray technique significantly enhances students' reading comprehension skills. This implies that English teachers should use this technique to enhance the students’ reading comprehension. However, the absence of a control group is a limitation of this research, and future research should address this limitation.